Cryptosporidium parvum in brown brocket (Mazama gouazoubira) from Brazil: First report of the subtype IIaA16G3R1 in cervids - Teixeira, Weslen Fabricio Pires [UNESP]; De Oliveira, Márcio Leite [UNESP]; de Faria Peres, Pedro Henrique [UNESP]; Nagata, Walter Bertequini [UNESP]; Santana, Bruna Nicoleti [UNESP]; Oliveira, Bruno César Miranda [UNESP]; Duarte, José Maurício Barbanti [UNESP]; Cardoso, Tereza Cristina [UNESP]; Lopes, Welber Daniel Zanetti; Bresciani, Katia Denise Saraiva [UNESP] (Elsevier, 2021)
This research had as objective to evaluate the occurrence and to characterize genetically the infections by Cryptosporidium in Mazama gouazoubira. By a non-invasive harvest methodology using trained sniffer dogs to locate fecal samples of cervids, 642 fecal samples were obtained from six Brazilian localities. The cervids species responsible for the excretion of each fecal sample were identified by the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), using the mitochondrial cytochrome b target gene (cyst b) and the restriction enzymes Sspl, AflIII and BstN. From this identification, 437 fecal samples of M. gouazoubira were selected for research of Cryptosporidium spp. performed through negative staining with malachite green and polymerase chain reaction (nPCR), with the subunit of 18S rRNA gene, followed by sequencing the amplified products. In the samples that were diagnosed the presence of parasite species with zoonotic potential, genotyping was also performed using nPCR with the subunit of GP60 gene. Statistical analysis consisted of the Fisher exact test to verify the association of the presence of the enteroparasite in relation to the presence of cattle in each locality, and the McNemar tests and Kappa correlation coefficient used to compare the results obtained between the two diagnostic techniques. In the fecal samples of M. gouazoubira the occurrences of Cryptosporidium were diagnosed in 1.6% (7/437) and 1.1% (5/437), respectively, through nPCR and microscopy. Cryptosporidium. parvum was diagnosed in 100% (7/7) of the samples submitted to sequencing (18S gene). The IIaA16G3R1 subtype was diagnosed in five of the C. parvum samples submitted to genotyping (GP60 gene). This is the first world report of C. parvum in M. gouazoubira and subtype IIaA16G3R1 in cervids.
Keywords: Brazil; Cryptosporidium parvum; Genotyping; Mazama gouazoubira; Subtype IIaA16G3R1